Reinforced nanowrinkle electrospun photothermal membranes via solvent‐induced recrystallization - Jinlin Chang; Weiling Wang; Zhaoxin Li; Yujiao Wang; Yacong Hou; Zhiyuan Cao; Zhenwei Liang; Yuan Ma; Ding Weng; Jun Song; Yadong Yu; Lei Chen; et al. (EcoMat, 2024)
Abstract Wearable photothermal materials can capture light energy in nature and convert it into heat energy, which is critical for flexible outdoor sports. However, the conventional flexible photothermal membranes with low specific surface area restrict the maximum photothermal capability, and loose structure of electrospun membrane limits durability of wearable materials. Here, an ultrathin nanostructure candle soot/multi‐walled carbon nanotubes/poly (L‐lactic acid) (CS/MWCNTs/PLLA) photothermal membrane is first prepared via solvent‐induced recrystallization. The white blood cell membrane‐like nanowrinkles with high specific surface area are achieved for the first time and exhibit optimal light absorption. The solvent‐induced recrystallization also enables the membrane to realize large strength and durability. Meanwhile, the membranes also show two‐sided heterochromatic features and transparency in thick and thin situations, respectively, suggesting outstanding fashionability. The nano‐wrinkled photothermal membranes by novel solvent‐induced recrystallization show high flexibility, fashionability, strength, and photothermal characteristics, which have huge potential for outdoor warmth and winter sportswear.